CRMP4 CpG Hypermethylation Predicts Upgrading to Gleason Score ≥ 8 in Prostate Cancer - Qin, Xiao-Ping; Lu, Qi-Ji; Yang, Cheng-Huizi; Wang, Jue; Chen, Jian-Fan; Liu, Kan; Chen, Xin; Zhou, Jing; Pan, Yu-Hang; Li, Yong-Hong; Ren, Shan-Cheng; Liu, Jiu-Min; et al. (Frontiers in Oncology, 2022)
Background: This study determined the predictive value of CRMP4 promoter methylation in the prostate tissues collected by core needle biopsies for a postoperative upgrade in GS to ≥8 . Method: The pathologic factors correlated with the postoperative GS upgrade to ≥8 were analyzed by logistic regression. The cut-off value for CRMP4 promoter methylation in the prostate tissues collected by core needle biopsy was estimated from the ROC curve in patients with a postoperative GS upgrade to ≥8. Result: Multivariate logistic regression showed that prostate volume, number of positive cores, and CRMP4 promoter methylation were predictive factors for a GS upgrade to ≥8 (OR: 0.94, 95% CI: 0.91-0.98, P=0.003; OR: 3.16, 95% CI: 1.81-5.53, P<0.001; and OR: 1.43, 95% CI: 1.32-1.55, P<0.001). The positive predictive rate was 85.2%, the negative predictive rate was 99.3%, and the overall predictive rate was 97.9%. The ROC curve showed that CRMP4 promoter methylation had the highest predictive value for GS upgrade. When the CRMP4 promoter methylation rate was >18.00%, the low-risk PCa patients were more likely to escalate to high-risk patients. The predictive sensitivity and specificity were 86.9% and 98.8%, respectively. The area under the ROC curve (AUC) was 0.929 (P<0.001). The biochemical recurrence (BCR)-free survival, progression-free survival, and cancer-specific survival (CSS) were worse in patients with a postoperative GS upgrade to ≥8 than in patients without an upgrade (P<0.001 for each). The Kaplan-Meier survival analysis indicated that the BCR-free survival, progression-free survival, and CSS were worse in patients with CRMP4 methylation >18.0% than in patients with CRMP4 methylation ≤18.0% . Conclusion: A CRMP4 promoter methylation rate >18.00% in prostate cancer tissues indicated that patients were more likely to escalate from low-to-high risk after undergoing a RP. In addition, the seminal vesicle invasion rate based on postoperative pathology, positive resection margin rate, positive lymph node involvement rate, BCR, clinical progression rate, and cancer-specific (CS) death rate were higher in patients with a postoperative GS rate to ≥8 than in patients without an upgrade. The BCR-free survival, progression-free survival, and CSS were worse in patients with CRMP4 methylation >18.0% than in patients with CRMP4 methylation ≤18.0%.